Psychological Analysis of Elsa’s Character in Novel “My Grandmother Asked Me to Tell You She’s Sorry” by Fredrik Backman - Gultom, Yessy Frietama; Retnomurti, Ayu Bandu; Kurniawaty, Julia Bea (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
The objectives of this study are to describe the psychological aspects of the character's story and identify the many forms of psychology exhibited by the main character in the novel